PARTICULARITIES OF CIVIL ACTION IN THE CASE OF FRAUD BY BANK CREDIT CONTRACTS - Andrei-Viorel IUGAN (Challenges of the Knowledge Society)
The crime of fraud is one of the most important threats facing the contemporary Romanian society. One of the most common ways of fraud is fraud through credit agreements. Of course, as in any criminal proceedings, in this case the question arises as to the way of repairing the damage caused by the offense. The particularity of solving the civil action in this case is the fact that, according to Romanian law, the credit contract is an executory title, so the bank would have no reason to wait for the criminal trial because it can immediately proceed to the forced execution of the person who obtained the credit in fraudulently. However, there is also the view that the criminal court will have to cancel the credit agreement, which has been hit by absolute nullity at the end of the criminal trial, and to oblige the defendant to pay damages. Throughout this study, we will try to analyze the consequences of both solutions and try to identify the legal and sound solution.